Development of Pascal Principle Activities Using The Stem Approach and Undergraduate Physics Students’ Perception Towards The Activities - Nawwar Raihan Alias; Nurulhuda Abd Rahman (PILLAR OF PHYSICS EDUCATION, 2021)
The aim of this study was to develop Pascal Principle teaching and learning activities using the STEM approach and to determine the content validity and undergraduate Physics students’ perception of the activities. This study was a developmental research using ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model to develop the activities. The population was 135 physics undergraduates in their fifth and seventh semester of study from one of the public universities in Malaysia. Data was collected using a questionnaire that was adapted from a standardised instrument and that was distributed using Google Form to the population together with a link to the activities. The response rate was 29.6% (40 respondents). Perception data were analysed descriptively using percentage for content, language, design, and interest. Result shows that the experts were 95.5% in agreement about the content validity of the activities. For the perception data, 98.5%, 99.5%, and 99.0% students have positive perceptions towards the content, language, and design, respectively. In addition, 96.3% show interest in the activities. In conclusion, the research succeeded in developing validated teaching and learning activities that use the STEM approach and that were perceived positively by physics undergraduates. The materials for the activities can thus be used as a teaching and learning resource in the classroom.